Analisis Manfaat Kegiatan Musrenbang terhadap Pembangunan Desa dan Kelurahan di Kecamatan Namorambe Deli Serdang - Faiz Berampu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to find out housing policies and residential areas, the legal framework for housing facilities, public institutions and services, the provision of housing facilities, public institutions and services such as laws and procedures for providing public housing, housing work. and work. The research method used is very good, while the source of information is the staff of the Deli Serdang Regency Housing and Development Office. The data analysis process is carried out by means of a data reduction process, presenting data and drawing conclusions, validating the data that has been collected and expressed in the form of a report. Research findings indicate factors that help and hinder, including communication skills between the parties responsible for implementing the plan, namely employees. In the field of public housing and maintenance work. Deli Serdang Regency and land owners, as well as employees have the right to resolve problems that arise in the process of handing over resources, equipment and public services (PSU) to the Deli Serdang Regency Government.